Autochthonous Babesia canis infections in 49 dogs in Germany. (11th January 2023) - Weingart, Christiane; Helm, Christina S.; Müller, Elisabeth; Schäfer, Ingo; Skrodzki, Marianne; von Samson‐Himmelstjerna, Georg; Krücken, Jürgen; Kohn, Barbara
Abstract: Background: Vector‐borne diseases are of increasing importance in Germany. Since 2015, autochthonous cases have been increasingly documented in Berlin/Brandenburg. Objectives: Describe autochthonous Babesia canis infection in the Berlin/Brandenburg region. Animals: Forty‐nine dogs with autochthonous B. canis infection. Methods: Evaluation of history, clinical signs, laboratory abnormalities, treatment, and outcome. Results: Dogs were presented between March and August (9) and September and January (40) in the years 2015‐2021. Historical and clinical findings were lethargy (100%), pale mucous membranes (63%), fever (50%), and pigmenturia (52%). Common clinicopathological findings were thrombocytopenia (100%), anemia (85%), intravascular hemolysis (52%), pancytopenia (41%), and systemic inflammatory response syndrome (SIRS; 37%). Babesia detection was based on blood smear evaluation (n = 40) and PCR targeting the 18S rRNA gene of piroplasms (n = 49). Sequencing indicated 99.47% to 100% identity to B. canis sequences from GenBank. All dogs were treated with imidocarb (2.4‐6.3 mg/kg; median, 5 mg/kg); 8 dogs received 1, 35 received 2, and 1 dog each received 3, 4, or 5 injections, respectively. Continued PCR‐positive results were detected in 7 dogs after the 1st, in 5 after the 2nd, in 2 after the 3rd, and in 1 28 days after the 4th injection. Four dogs were euthanized and 3 dogs died. Conclusions and Clinical Importance: Autochthonous B. canis infections in Berlin/Brandenburg were associated with severe clinicopathological changes, SIRS, and multiorgan involvement. Testing by PCR during and after treatment is advisable to monitor treatment success. Screening of blood donors in high‐risk areas and year‐round tick protection is strongly recommended.